Tempat Persarangan Lebah Hutan (Apis dorsata F.) di Pulau Sermata - Masauna, Esther D; Utuwaly, Imas D; Jaya, Firman; Lastriyanto, Anang; Yunus, Mochammad; Batoro, Jati; Erwan, Erwan; Masyithoh, Dewi; Ustadi, Ustadi; Lamerkabel, Jacobus S. A. (Fakultas Pertanian, Universitas Pattimura, 2024)
The aim of the study was to determine the nesting sites of Apis dorsata (F) forest bees. the method used in this research was a descriptive survey. The results showed that trees and rock cliffs are nesting sites for forest bees on the island of Sermata. The Banyan tree is a tree that is preferred as a nesting place for forest bees (4 trees) in addition to Mango trees (2 trees), Salawaku (2 trees) , Kemiri (1 tree) , and Parna (1 tree). The height of the nesting places of forest bee colonies on trees and rock cliffs from the ground is at an altitude of 2.82 m to 27.40 m. The mango tree is the lowest forest bee nesting tree, while the highest is found in the banyan tree (20.51 m) and rock cliff 27.40 m. The habitat for the most forest bee colonies was 95 colonies in the range > 0-100 masl and 20 colonies in the range > 100-200 masl. The number of forest bee nests found in the locations of the villages of Regoha, Rotnama, Lelang, and Elo was 115 colony nests.